(untitled) (LACCEI, 2024)
Research that aims to evaluate the physical and mechanical properties of concrete pavers f’c=420 kg/cm2 by adding demolition residues, applied research, experimental design, the sample was 144 pavers. It is concluded that the physical and mechanical properties of concrete pavers f’c=420 kg/cm2 , improve significantly in the additions of 20%, 40% and 60% of demolition residues